ЎЗБЕК ТИЛИНИ ЎҚИТИШДА НУТҚИЙ КОМПЕТЕНЦИЯНИ ШАКЛЛАНТИРУВЧИ ЎҚУВ ТОПШИРИҚЛАРИ МАЗМУНИНИНГ ЛИНГВОДИДАКТИК ХУСУСИЯТЛАРИ - Юсупов, А.; Юсупова, Г. (SCIENCE and SOCIETY, 2019)
The question of the content of education is one of the oldest and most relevant issues in human history. This is natural because at all stages of development people ask, “What to teach?”. The answer to this question has always been one of the important ones. While learning content is understood as part of a rich social experience chosen for learning and methodically designed for teaching students the other group of scholars investigates the ways of its study.